국어사전에서의 형태 분석 정보 제시 방안 - 『표준국어대사전』을 중심으로 - 이준희(Lee, Jun Hee); 조교현(Cho, Gyo Hyeon); 박도리(Bak, Do Rhee); 곽유석(Kwak, Yuseok) (한국사전학, 2024)
국어사전에서 적절한 형태 분석 정보를 제공하면 단어에 대한 이해도를 높일 수 있을 뿐만 아니라, 형태 단위 검색을 통해 사전의 활용도도 높일 수 있다. 그러나 현재 『표준국어대사전』에서는 직접 성분 분석만을 제공하여 형태 분석 정보를 충분히 반영하고 있지 못하다. 본고는 『표준국어대사전』을 중심으로 형태 분석 정보를 제공할 수 있는 적절한 방안을 제안하는 것을 목적으로 하며, 실제 형태 분석이 진행된 결과를 통해 형태 분석 원칙을 검증하고자 한다. 적절한 형태 분석 정보를 제공하기 위하여 본고는 복합어의 내부 구조를 보다 잘 반영할 수 있는 다원 분석 방식과 규범 사전인 『표준국어대사전』의 특성을 반영하여 다음과 같은 형태 분석 원칙을 정립한다. 첫째, 표제어를 구성하고 있는 공시적인 형태소들을 분석한다. 둘째, 기구축된 어문 규범과 문법 정보를 반영하여 분석한다. 셋째, 참고 정보들과 유기적으로 연결될 수 있도록 분석한다. Using the Providing adequate morphological information in dictionaries can not only enhance the understanding of words but also reinforce the usage of dictionaries through morpheme-based searches. However, the current Standard Korean Dictionary(표준국어대사전) only provides descriptions of the immediate constituents of words, therefore not being able to fully reflect their morphological information. Using the SKD as a reference point, this paper aims to propose apposite measures to accommodate morphological information to dictionaries broadly, and seeks to establish several principles for representing morphological information. Such principles must acknowledge the characteristics of normative dictionaries, and take ultimate constituents of words into account. Thus, this paper suggests the following principles for morphological representations in dictionaries: (1) headwords should be analysed synchronically, (2) the representation should consider already-established linguistic norms and grammatical information, and (3) the analysed results should be able to organically associate with other reference information. KCI Citation Count: 0